Molecular Approaches to Genetic Diversity 2015
DOI: 10.5772/60423
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Genetic Diversity in Fish Using Molecular Markers

Abstract: Their extinct relatives (Infraclass Chondrostei) date to the Devonian (about 350 million years ago) and Acipenser fossils were found in the Western of North America dating from Upper Cretaceous. At present time within Acipenseriformes only two families exist, Acipenseridae and Polyodontidae, the first one counting 25 species inhabiting rivers, lakes, coastal waters and inner seas from the Northern hemisphere. The Acipenseriformes species are strictly Northern hemisphere fishes, some being resident to fresh wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 62 publications
0
8
0
2
Order By: Relevance
“…Molecular marker—in biology—is an expression for any stable heritable and detectable variation at the DNA level [ 5 ]. Molecular marker—on the gel image—is a polymorphic band that distinguishes between two groups of samples.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular marker—in biology—is an expression for any stable heritable and detectable variation at the DNA level [ 5 ]. Molecular marker—on the gel image—is a polymorphic band that distinguishes between two groups of samples.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there are no specific SSR markers for the Alosa genus in the Caspian Sea. The usefulness of SSR markers depends on their polymorphism information content, which reflects the ability of a marker to detect a polymorphism in a given population (Dudu et al, 2015). We have demonstrated that the six SSRs found in American shad ( Alosa sapidissima ) (Julian and Bartron, 2007) show a high rate of polymorphism (PIC = 0.90) in A. braschnikowi as well.…”
Section: Discussionmentioning
confidence: 99%
“…Klasifikasi penanda kedua adalah yang berkaitan dengan posisi mereka di dalam sel. Jadi kita dapat membedakan antara penanda nuklir dan mitokondria DNA (mtDNA), tergantung pada lokalisasi mereka dalam genom nuklir atau mitokondria (Dudu et al, 2015).…”
Section: Keragaman Genetikunclassified